The count of Monte Cristo - Dumas, Alexandre, 1802-1870. (New York : Simon & Brown, 2002)
Contents
Keywords: French fiction; Fransız romanı; France -- History -- 19th century -- Fiction; Fransa -- Tarih -- 19. yüzyıl -- Roman